Greek writers and philosophers in Philo and Josephus: a study of their secular education and educational ideals - Koskenniemi, Erkki (Studies in Philo of Alexandria, 2019)
Intro -- ‎Contents -- ‎Preface -- ‎Chapter 1. Introduction -- ‎1. The Task of the Study -- ‎2. A Brief History of the Research -- ‎3. The Outline of Graeco-Roman Education -- ‎4. A More Precise Definition of the Task -- ‎Chapter 2. Philo: Offspring from Sarah and Hagar -- ‎1. Introduction -- ‎2. Philo and Greek Writers -- ‎2.1. Introduction -- ‎2.2. Philo, Poets and Dramatists -- ‎2.2.1. Greek Poets -- ‎2.2.1.1. Homer -- ‎2.2.1.2. Hesiod -- ‎2.2.1.3. Solon -- ‎2.2.1.4. Theognis -- ‎2.2.1.5. Pindaros -- ‎2.2.1.6. Unidentified Poets -- ‎2.2.1.7. Poets in General -- ‎2.2.2. Classical Drama -- ‎2.2.2.1. Aeschylus -- ‎2.2.2.2. Sophocles -- ‎2.2.2.3. Euripides -- ‎2.2.2.4. Ion -- ‎2.2.2.5. Epicharmus -- ‎2.2.2.6. Menander -- ‎2.2.2.7. Theatre in General -- ‎2.2.3. Summary -- ‎2.3. Philo and Philosophers -- ‎2.3.1. Pre-Socratic Philosophers -- ‎2.3.1.1. The Seven Sages in General -- ‎2.3.1.2. Bias -- ‎2.3.1.3. Thales and Other Natural Philosophers -- ‎2.3.1.4. Solon -- ‎2.3.1.5. Pythagoras and the (Neo)Pythagoreans -- ‎2.3.1.6. Zeno the Eleatic -- ‎2.3.1.7. Heraclitus -- ‎2.3.1.8. The Sophists -- ‎2.3.1.9. Anaxagoras -- ‎2.3.1.10. Democritus -- ‎2.3.1.11. Empedocles -- ‎2.3.2. Socrates and Plato -- ‎2.3.2.1. Socrates -- ‎2.3.2.2. Plato -- ‎2.3.3. Aristotle and the Peripatetic School -- ‎2.3.4. The Socratic Schools and Hellenistic Schools -- ‎2.3.4.1. Cynics -- ‎2.3.4.2. The Hedonists / the Cyreneans -- ‎2.3.4.3. Epicurus and the Epicureans -- ‎2.3.4.4. Stoics -- ‎2.3.4.5. Sceptics -- ‎2.3.5. Other Greek Philosophers -- ‎2.3.6. Exotic Philosophers -- ‎2.3.7. Summary -- ‎2.4. Other Writers Cited -- ‎2.5. Conclusion -- ‎3. Philo's Educational Ideals and His Own Witness -- ‎4. Jews and the Secular Education in Alexandria -- ‎5. Conclusion -- ‎Chapter 3. Josephus: It Is Difficult to Transplant an Old Tree -- ‎1. Introduction -- ‎2. Josephus and Greek Writers.